3D carboxyl and hydroxyl co-enriched graphene hydrogels as binder-free electrodes for symmetric supercapacitors. (3rd September 2019) - Zhang, Yong; Wen, Guangwu; Fan, Shan; Ma, Wenhui; Li, Shuhua; Wu, Tao; Yu, Zhaochuan; Zhao, Baoru
Abstract: At present, amino acids are often used as the source of heteroatom functional groups for the preparation of doped graphene materials. However, a large amount of amino acids will be used as reaction precursors in the preparation process, which will lead to increased cost, reduced efficiency and waste of resources. Herein, a very small amount of neutrall -alanine is employed to synthesize 3D carboxyl and hydroxyl co-enriched graphene hydrogels (CHGHs) by a one-pot hydrothermal method. The CHGHs contain copious carboxyl and hydroxyl groups, and a small amount of nitrogen-containing functional groups. In addition, the CHGHs also present large specific surface areas and 3D porous structures. Therefore, the CHGH-20 binder-free electrode displays a high specific capacitance of 262.8 F g −1 at 0.3 A g −1, and this value still maintains 84.3% (221.6 F g −1 ) at 10 A g −1 in a two-electrode system in 6 M KOH. Furthermore, the CHGH-20 electrode also displays outstanding cycle stability with 103.6% of its initial capacitance after 10, 000 cycles at 10 Ag −1 . Therefore, the CHGHs samples prepared by a very small amount of neutrall -alanine have great significance for the practical application of supercapacitors. Graphical abstract: Image 1 Highlights: CHGHs samples are easily prepared via a one-pot hydrothermal method. CHGHs samples have 3D porous structures and high specific surface areas. CHGHs samples have high content of carboxyl and hydroxyl groups. The CHGH-20 based electrode shows a high specific capacitance of 262.8 F g −1 . The CHGH-20 based symmetric supercapacitor displays outstanding cycle stability.